Do Patients Go Home at Their Own Request? A Study of the Quality of Hospital Services during the Covid-19 Pandemic - Napirah, Muhammad Ryman; Vidyanto, Vidyanto (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Covid-19 is categorized as a non-natural disaster. At the Undata Palu Regional General Hospital (RSUD), there are still problems related to PAPS (Going Home On Own Request), so this needs serious attention from the hospital. The purpose of this study was to determine the relationship of service quality from the aspect of physical evidence (tangibles), responsiveness (responsiveness), reliability (reliability), assurance (assurance), and empathy (empathy) with the desire to go home on their request (PAPS) patients during the period the covid-19 pandemic in the inpatient unit of Undata Hospital Palu. This type of research was an analytic survey with a cross-sectional approach. The sample in this study was all inpatients at Undata Hospital Palu, totaling 96 people, with an accidental sampling technique. The data were collected and analyzed using computer-based software in univariate and bivariate ways. The results showed that there was a relationship between service quality from the aspect of physical evidence (tangibles) (p=0.002), responsiveness (p=0.049), reliability (p=0.001), assurance (p=0.005), and empathy (p = 0.018) with the desire to go home on own request (PAPS) of patients during the covid-19 pandemic in the inpatient unit of Undata Hospital Palu. It is hoped that the Undata Palu Regional General Hospital can improve the quality of service and reduce patients who go home at their own request by improving better service standards, which are, of course, following Islamic values to serve others.